HUBUNGAN OBESITAS SENTRAL DENGAN SIKLUS MENSTRUASI DAN DYSMENORRHEA PRIMER PADA REMAJA - Karina S, Else; Nuryanto, Nuryanto; Kusumastuti, Aryu Candra (Journal of Nutrition College, 2017)
Background: Irregular menstrual cycle and primary Dysmenorrhea are menstrual disorder which woman can sustain. These can be occur because nutritional status especially obesity. Central obesity increase in adolescent which describe high body fat mass. High percentage of body fat mass in central obese patients can lead to hormonal dysfuntion and causing abnormal menstrual cycles and primary Dysmenorrhea. Objective: To analyze the association of central obesity with menstrual cycle and primary dysmenorrhea in adolescentsMethods : this study used Cross sectional design with 73 subject central obesity and 73 normal adolescent based on waist circumference. Anthropometric measurementsÂ include height, weight and waist circumference. Physical activity assessed by GPAQ physical activity questionnaire, family history Dysmenorrhea, menstrual cycle and primary Dysmenorrhea were assessed by questionnaire. Data were analyzed by Chi Square test.Results: There were 23 adolescents or 31.5% of central obesity group have abnormal menstrual cycle whereas in normal group there were 10 adolescent or 13.6% who have abnormal menstrual cycle. There was association between central obesity and menstrual cycle ( p = 0.018). There were 20 adolescents or 27.3% central obesity group have primary Dysmenorrhea whereas in normal group there were 15 adolescents or 20.5%. There was no significant association between central obesity and primary Dysmenorrhea ( p = 0.43).Conclusion : There was association between central obesity and menstrual cycle but there was not association between central obesity and menstrual cycle